STUDY OF WATER PHYSICS, CHEMISTRY, AND BIOLOGY QUALITY IN SWAMP WATER HIGH TIDE CONDITIONS IN BANYUASIN REGENCY, SOUTH SUMATERA - Sa'adah, Raudhatus; Puteri, Rizki Eka; Sari, Selly Ratna (University of Lampung, 2021)
This study was conducted in tidal lowland at Banyu Urip Village, Tanjung Lago District, Banyuasin Region, South Sumatera. Samples were collected two times. The water sample was collected during high tide in primary, secondary, and tertiary canals. The result showed the seasonal variation of physical and chemical water parameters such as temperature 27 – 30 ºC, pH 3 – 5, DO 3.7 – 4.5 mg/l, phosphate 0.01 – 0.02 mg/l, TSS 108 – 232 mg/l, and EC 11 – 107 µmhos/cm. This study also identified 10 classes and 10 genera of phytoplankton. It has potential as a natural food source. The result revealed that physical and chemical water quality parameters were still suitable for aquaculture based on Government regulation of Republic Indonesia number 82 year 2001 about water criteria class III for fisheries. Meanwhile, the great challenge of tidal lowland for fishery management is low pH. Therefore, pre-treatment to increase pH before fish rearing is required.